Thermodynamic evaluation of the impact of DNA mismatches in PCR-type SARS-CoV-2 primers and probes. (April 2021) - Miranda, Pâmella; Weber, Gerald
Abstract: Background: DNA mismatches can affect the efficiency of PCR techniques if the intended target has mismatches in primer or probe regions. The accepted rule is that mismatches are detrimental as they reduce the hybridization temperatures, yet a more quantitative assessment is rarely performed. Methods: We calculate the hybridization temperatures of primer/probe sets after aligning to SARS-CoV-2, SARS-CoV-1 and non-SARS genomes, considering all possible combinations of single, double and triple consecutive mismatches. We consider the mismatched hybridization temperature within a range of 5 ∘ C to the fully matched reference temperature. Results: We obtained the alignments of 19 PCR primers sets that were recently reported for the detection of SARS-CoV-2 and to 21665 SARS-CoV-2 genomes as well as 323 genomes of other viruses of the coronavirus family of which 10 are SARS-CoV-1. We find that many incompletely aligned primers become fully aligned to most of the SARS-CoV-2 when mismatches are considered. However, we also found that many cross-align to SARS-CoV-1 and non-SARS genomes. Conclusions: Some primer/probe sets only align substantially to most SARS-CoV-2 genomes if mismatches are taken into account. Unfortunately, by the same mechanism, almost 75% of these sets also align to some SARS-CoV-1 and non-SARS viruses. It is therefore recommended to consider mismatch hybridization for the design of primers whenever possible, especially to avoid undesired cross-reactivity. Highlights: We calculated hybridization temperatures of primers aligned to SARS-CoV-2 genomes with up to 3 consecutive mismatches. It was found that in many cases, near complete coverage is only achieved when mismatches are taken into account. We also considered alignments to non-SARS genomes and found non-negligible cross-reactivity in nearly 75% of the primer sets.